165 What Is the Effect of Open vs Percutaneous Screws on Complications Among Patients Undergoing Lateral Interbody Fusion for Adult Spinal Deformity?. (August 2016) - Than, Khoi Duc; Nguyen, Stacie; Park, Paul; Chou, Dean; La Marca, Frank; Uribe, Juan S.; Vogel, Todd Douglas; Nunley, Pierce D.; Eastlack, Robert; Anand, Neel; Kanter, Adam S.; Mummaneni, Praveen V.; et al.
Abstract : INTRODUCTION: This study aims to compare differences in incidence and type of complications (COMP) between circumferential minimally invasive surgery (cMIS, ie MIS transforaminal lumbar interbody fusion [TLIF] and/or lumbar lateral interbody fusion [LLIF] with MIS screws) and hybrid approaches (HYB, ie MIS LLIF ± with open screws). METHODS: A retrospective review of a multicenter MIS deformity database was performed. Inclusion criteria for this database: age >18 years, and at least one of the following: coronal Cobb angle (CCA) >20, SVA >5 cm, PI-LL >10, and PT > 20. Only patients who underwent cMIS or HYB approaches were included for this study, and were propensity matched by levels instrumented. RESULTS: Of 420 patients that met inclusion criteria, 165 had complete data. One hundred thirty-seven were available for analysis after excluding 3 column osteotomies and 76 remained after propensity matching (38 cMIS and 38 HYB). There were no differences in demographics, number of levels instrumented (6.8 HYB vs 6.1 cMIS; P = .622), and pre- and postoperative radiographic results. HYB had significantly longer OR time (623 vs 490 minutes; P = .015) and larger expected blood loss (1396 vs 637; P = .001). 55.3% of HYB vs 44.7% cMIS patients experienced at least 1 COMP ( P = .359). cMIS patients had significantly fewer neurological ( P = .044), operative ( P = .005), and minor ( P = .034) COMPs. Reoperation was similar between groups (28.9% HYB, 26.3% cMIS). The most common COMP for cMIS was radiographic (n = 10; 6 with pseudoarthrosis) and neurological for HYB (n = 11; 8 with radiculopathy). Both groups saw improvement from pre- to postoperative Oswestry Disability Index, visual analog scale (VAS) back and leg (all P < .05); however, cMIS had a greater reduction in VAS leg ( P = .002). CONCLUSION: The overall COMP rate between cMIS and HYB is similar. cMIS surgery results in significantly fewer neurological, operative, and minor COMPs, Reoperation rates were similar, and, despite complications, patients saw significant improvement in pain and function.